Implementation of Finite State Machine to Determine The Behaviour of Non-Playabale Character in Leadership Simulation Game - Rizqi Alvian, Muhammad Bagus; Bukhori, Saiful; Furqon, Muhammad ‘Ariful (Journal of Games, Game Art, and Gamification, 2024)
In today's era, games are widely enjoyed by the Indonesian society, and one of them is simulation games. Simulation games have many advantages, including allowing players to experiment freely and encouraging them to learn. Therefore, the use of simulation games can be utilized as a training medium, such as leadership training. There are five levels of leadership based on The 5 Levels of Leadership: position, permission, production, people development, and pinnacle. Direct practice is necessary in training these levels of leadership through the implementation of Artificial Intelligence (AI) in simulation games. One of the AIs used for this implementation is the Finite State Machine (FSM). FSM will be implemented in Non-Playable Characters (NPCs) to determine behavior that is adjusted to the 5 levels of leadership. There are three State Machines (SM) applied to NPCs: Core Game SM, Movement SM, and Status SM. The use of FSM in NPCs results in dynamic NPC behavior in terms of physical movement and changes in NPC status according to 5 Levels of Leadership